Pengelolaan Pembelajaran Berbasis Loose Parts dalam Meningkatkan Kualitas Belajar - Fajri Dwiyama; Satma Awaliana (Adaara: Jurnal Manajemen Pendidikan Islam, 2021)
At the beginning of 2020 the whole world was hit by the COVID-19 outbreak. This pandemic affects almost all sectors of human life. The world of education in Indonesia has not been spared the impact of the pandemic. Likewise with the Pattola Palallo Kindergarten, the many obstacles faced caused the decline in the quality of learning at the Pattola Palallo Kindergarten. Therefore, the teacher tries to use a learning method that is considered capable of stimulating growth and all aspects of child development. Where, this method is expected to be able to be applied both at school through face-to-face, and at home through distance learning, so that the quality of learning in TK Pattola Palallo can be improved. The method in question is a loose parts based learning method. Loose parts based learning method is a learning method that uses media in the form of materials around us that can be separated and arranged into one, aligned, easy to combine with other materials and easy to carry and move. After the loose parst-based learning method is applied, the results show that this method can increase children's creativity, encourage children to be active in their learning so as to improve their physical motor development, increase children's independence, and train children's ability to work together, as well as build self-confidence in children, provide stimulation of all aspects of child development so as to improve children's learning outcomes. This learning method can be applied at school or at home because the media is easy to obtain and its implementation is done by playing, making it very easy for parents to accompany their children.